Biostratigraphy and biochronology of the Monte Hermoso Formation (early Pliocene) at its type locality, Buenos Aires Province, Argentina - Tomassini, Rodrigo Leandro (2013)
The Monte Hermoso Formation, cropping out at its type locality of Farola Monte Hermoso (Buenos Aires Province), is a classical fossiliferous unit of the South American Neogene, highlighted by the abundance and diversity of its vertebrate remains. However, its biostratigraphy and age have been largely debated, and numerous discrepancies and controversies have been stated. In this regard, the result of the analysis of new materials recovered from the different levels of this formation, following a strict control of stratigraphic provenance, is here reported. As well, the provenance of specimens of previous collections has been evaluated. The studied assemblage consists of Osteichthyes, Amphibia, Reptilia, Aves and Mammalia. These latter are the most numerous and belong to the Didelphimorphia, Polydolopimorphia, Rodentia, Notoungulata, Litopterna and Xenarthra. The recorded taxa suggest no important faunistic variations among the different levels of the Monte Hermoso Formation that would imply significant chronological differences, and hence, justify the recognition of two biostratigraphic units. The analysis of the first and last records as well as the taxa considered as exclusive, does not support the validity of the biozones of Trigodon gaudryi and Neocavia depressidens previously proposed. On this basis, a new scheme for the Monte Hermoso Formation at its type locality is proposed, including a new single biostratigraphic unit. This unit is the Eumysops laeviplicatus Range Zone, which represents the biostratigraphic base for the Montehermosan Stage/Age of the early Pliocene.